Multimodalitas Dalam Unggahan Dakwah Instagram @dasadlatif1212 - Surya Anantatama Sembiring (FAI UIM, 2023)
Multimodality has become a means of consuming messages in the era of social media. Content creators utilize text, audio and visuals to send messages. The message conveyed can now transcend the limitations of space and time. Ustaz Das'ad Latif often shares unique content on his Instagram account. One of them is an animation upload on his Instagram @dasadlatif1212. Social semiotic analysis helps to find effective semiotic sources and analyze how they are used in managing semiotic resources. The semiotic sources analyzed are the representational, interactive and compositional meanings that appear in semiotic sources. Semiotic resources that are managed well can be used in the current era of social media. In the future, it is hoped that young preachers will be able to take advantage of the increasingly fast-growing preaching media. Because preaching does not always have to be on the pulpit but can now be done via mobile devices. So whenever and wherever Mad'u needs them they can consume it.